Okoljski nadzorni sistem - model vrednotenja zakritih zavetij - Arthur, J. Howard (Strojniški vestnik, 2003)
Mathematical algorithms have been developed as the foundation of an environmental assessment model for mobile shelters. The assessment model can be used for sizing the heating and cooling equipment and for evaluating the transient thermal responses of shelters under specified initial heat-up and cool-down conditions. This model differs from standard HVAC load models in theform of the transient responses that can be predicted for the shelter. Currently available commercial and public-domain HVAC models predict transient-load variations and energy usage based upon a fixed inside design temperature. Computer codes such as TRNSYS can predict transient indoor conditions, but require detailed input, which is usually not available for thetypical shelter. The new, shelter environmental assessment model has the ability to predict inside temperature as a function of variations in environment condition, HVAC equipment performance, and inside load conditions. The algorithms use a multi node lumped capacity model for the shelter walls, the equipment and the air inside the shelter, since each of these elements has an energy-storage capacity. The model includes provisions for modeling camouflage netting as a thermal radiation shield having a negligible energy-storage capacity. Therefore, radiation-shield temperatures are computed from iterative, steady-state energy balances for each time step. The unknown temperatures for the elements with heat capacity are calculated ateach point in time using a "marching" solution combined with the radiation-shield temperatures. The model is designed to accommodate the energygains from equipment and personnel, and HVAC equipment operational features, with weather data for a specific location or from standard outdoor environmental conditions.
Keywords: natural environment; okolje; sistemi nadzorni; algoritmi matematični; zavetja; modeli vrednotenja; prenos toplote; nadzorni sistemi; algoritmi